Effects of Ti/Co and Co/Ti systems on the germanosilicidation of poly-Si capped poly-Si1−xGex substrate - Li, Y. S. (2013)
Ti/Co and Co/Ti bilayered systems were used for the formation of Co germanosilicide on polysilicon buffered poly-Si1−xGex (x=0.2, 0.3) gate stacks. In both cases, substantial Ge was found to segregate to the grain boundaries at the surface of the polycrystalline silicide (i.e., CoSiGe) films, resulting in a substantial degradation in the sheet resistance and a poor quality of the silicide films. It is shown that Ge is probably being expelled from the poly-SiGe grain and segregates to the grain boundaries during the annealing process, leading to the undesirable sheet resistance and poor film morphology observed from the Co germanosilicide films.